2023
DOI: 10.7150/ijbs.69784
|View full text |Cite
|
Sign up to set email alerts
|

FCN3 inhibits the progression of hepatocellular carcinoma by suppressing SBDS-mediated blockade of the p53 pathway

Abstract: Hepatocellular carcinoma (HCC) is the third-leading cause of cancer deaths globally. Although considerable progress has been made in the treatment, clinical outcomes of HCC patients are still poor. Therefore, it is necessary to find novel prognostic factors upon which prevention and treatment strategies can be formulated. Ficolin-3 (FCN3) protein is a member of the human ficolin family. It activates complement through pathways associated with mannose-binding lectin-associated serine proteases. Herein, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The overexpression of FCN3 has been shown to inhibit cell proliferation and induce apoptosis via the p53 signaling pathway 26 . A proposed mechanism is that FCN3 modulates the nuclear translocation of eukaryotic initiation factor 6 (EIF6) by binding to ribosome maturation factor (SBDS), which then leads to activation of the p53 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of FCN3 has been shown to inhibit cell proliferation and induce apoptosis via the p53 signaling pathway 26 . A proposed mechanism is that FCN3 modulates the nuclear translocation of eukaryotic initiation factor 6 (EIF6) by binding to ribosome maturation factor (SBDS), which then leads to activation of the p53 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A proposed mechanism is that FCN3 modulates the nuclear translocation of eukaryotic initiation factor 6 (EIF6) by binding to ribosome maturation factor (SBDS), which then leads to activation of the p53 pathway. In addition, Y-box binding protein 1 (YBX1) has been shown to regulate the translation and transcription of FCN3 to SBDS 26 . These results indicate that the FCN3/YBX1/SBDS axis may be a novel therapeutic target for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2, the activation of p53 mainly involves biological mechanisms such as acetylation and phosphorylation, while the inactivation of p53 is closely related to its ubiquitination, ubiquitination, and partial dephosphorylation 1,137 . At the same time, various proteins are not only activated by the transcription of p53 but also participate in the regulation of p53 activation or inactivation 138 . p53 and these proteins constitute a complex feedback regulatory network, including Siva1, 139 COP1, 140 Pirh2, 140 cyclin G, 141 ΔNp73, 142 and so on, as well as the classic MDM2 143 …”
Section: Activation and Inactivation Of P53mentioning
confidence: 99%
“… 1 , 137 At the same time, various proteins are not only activated by the transcription of p53 but also participate in the regulation of p53 activation or inactivation. 138 p53 and these proteins constitute a complex feedback regulatory network, including Siva1, 139 COP1, 140 Pirh2, 140 cyclin G, 141 ΔNp73, 142 and so on, as well as the classic MDM2. 143 …”
Section: Activation and Inactivation Of P53mentioning
confidence: 99%
“…Imbalances in plasma protein expression are frequently linked to pathological processes, particularly tumorigenesis. Numerous studies have reported positive (16)(17)(18)(19)(20)(21)(22)(23) or negatively (24)(25)(26)(27)(28)(29)(30)(31)(32)(33) correlations between plasma protein levels and tumor development, indicating that plasma protein levels may be in uenced by tumors or play a role in promoting or inhibiting tumor growth.…”
mentioning
confidence: 99%